Properties of a novel carbenicillin-hydrolyzing beta-lactamase (CARB-4) specified by an IncP-2 plasmid from Pseudomonas aeruginosa. - Philippon, A M (1986)
CARB-4, a novel carbenicillin-hydrolyzing beta-lactamase with an isoelectric point of 4.3, was discovered in a strain of Pseudomonas aeruginosa from France. It was determined by a multiresistant transmissible plasmid belonging to the P-2 incompatibility group.